Partisipasi Indonesia dalam IE-CEPA: Sebuah Kewajiban atau Kebijakan? - Carissa Amanda Siswanto; Wishnu Kurniawan; Dita Birahayu (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
International agreements made by Indonesia with other countries have helped enrich the provisions of legislation relating to trade and investment in Indonesia. One of them is IE-CEPA, it is hoped that the utilization of market share in each country can be optimized for entry into the European Union market and used as a basis to catch up with other ASEAN countries. The issue that arises here is whether Indonesia’s cooperation with the EFTA Group of Countries is an obligation or policy. This research uses a form of normative juridical research and uses a statute approach and a conceptual approach. The purpose of this study is to describe the cooperation carried out by Indonesia with the EFTA group of countries as an obligation of countries to implement economic policies. The results of this study show the cooperation carried out by Indonesia with the EFTA group of countries as part of economic policies to improve the country’s development. This cooperation agreement has been officially ratified into Indonesia’s national regulation through Article 1 of Law No.1/2021, which indicates the State’s approval to comply with and be bound by IE-CEPA. This is in accordance with Article 26 of VCLT and Article 4 paragraph (1) of Law No.24/2000.